The Relationship between Religious Coping and Resilience in Universitas Airlangga Medical Students Class of 2020 in Pandemic Time - Annisa Faradila; Azimatul Karimah; Irfiansyah Irwadi (Jurnal Psikiatri Surabaya, 2023)
Introductions: During the COVID-19 epidemic, college students were expected to adjust to varied daily routines, resulting in pressure and bad emotional sensations in each individual. This situation necessitates college students' attempts to better their survival through coping. Religion is one coping mechanism that may be used to help pupils reduce stress. The presence of resilience is another characteristic that can overcome any challenges. Coping is used to deal with stress caused by challenges, and spirituality is regarded as one part of developing excellent resilience. Objectives: Researchers decided to undertake a study to see whether there is a relationship between religious coping and resilience in the Faculty of Medicine, Universitas Airlangga students class of 2020 during a pandemic. Methods: This cross-sectional observational analytic study collects primary data using two questionnaire instruments, BRIEF RCOPE and Growth-Focused Resilience. Non-random sampling was used to collect samples from 208 Faculty of Medicine, Airlangga University students class of 2020. The Chi-Square Test was used to examine the data using the SPSS version 21 tool. Results: The p-value (sig) was 0.000 (0.05), indicating a significant connection between religious coping characteristics and resilience variables. Religious coping has been shown to be one of the variables affecting and associated with resilience; effective coping will lead to good growth and vice versa. Conclusions: It is possible to infer a substantial association between religious coping and resilience among the Faculty of Medicine, Universitas Airlangga students class of 2020.